A Bridgehead to Africa : German Interest in the Ottoman Province of Tripoli (Libya) 1884–1918 - Al Ghafal, Suaad Mohamed Omar (2021)
This monograph analyses the role of the province of Tripoli, Libya, in the context of German foreign politics with a focus on the period between 1884 and 1918. Suaad Alghafal examines the German military, political and economic strategy, and sheds lights on the international events that provided the setting for the German policy towards Libya, particularly the European ‘Scramble for Africa’.